(3GdeQGSdGJ hGdecGJHGJs - (3eMeO Hf YHO Gddg Hf SYjO GdSdeGfj GddhTj GdCUd, GdZQfGWj GdCfOdSj, CHh YHO Gddg, GdTgjQ HdSGf GdOjf GHf GdNWjH,J (B776 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI hGdOjHGLI hHfaSj heG faS Ydi HgjfI ajfRdfj Yfg GdecGS HCKeGf s
(3BNQgG (B:s
(3hdhSeYJ eG cfJ ai GdeMGd WeYJ hdcfJ eYJRd GdJUQja eLGfHG ddJMQja s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B235s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3eJaQbGJs